Redesign of a hand pallet truck by integrating ergonomics analysis and quality function deployment - Isa, Halim; Wan , Fadhli (Pan-Pacific Council on Occupational Ergonomics. Dept. of Ergonomics. IIES, UOEH, 1-1, Iseigaoka, Yahatanishi-ku, Kitakyushu, 8078555, JAPAN, 2009)
Today, materials handling devices (MHDs) that provide effective handling of goods have become important tools in industrial workplaces. Hence proper design of MHDs can increase productivity, minimize the risk of injury and improve the comfort of industrial workers. Sprains and strain are common injuries experienced by workers due to misuse or improper design of MHDs. In recognition the importance of the MHD design, this study conducted to redesign the existing MHD for pushing and pulling activities in manufacturing industry, using a hand pallet truck (HPT) as case study. Ergonomics analysis and Quality Function Deployment (QFD) were integrated to redesign the HPT so that it can fulfill workers’ requirements while reducing stresses on workers during pushing or pulling activities. Based on the findings, we conclude that the integration of ergonomics analysis and QFD is an effective and scientific solution in designing an ergonomic HPT.